Tree - Burnie, David; Chadwick, Peter; Dowell, Philip; Taylor, Kim 1933- (London New York DK, 2005)
Photographs and text explore the anatomy and life cycle of trees, examining the different kinds of bark, seeds, and leaves, the commercial processing of trees to make lumber, and the creatures that live in trees
"Discover the world of trees-- from tiny saplings to forest giants"--Cover
At head of title: Eyewitness
Includes index
3
Keywords: Trees -- Juvenile literature; Trees